Hepatic T1-time predicts cardiovascular risk in all-comers referred for cardiovascular magnetic resonance. (3rd October 2022) - Mascherbauer, K; Dona, C; Koschutnik, M; Dannenberg, V; Nitsche, C; Duca, F; Beitzke, D; Loewe, C; Waldmann, E; Trauner, M; Bartko, P; Goliasch, G; et al.
Abstract: Background: Liver damage is frequently observed in patients with cardiovascular disease (CVD) but infrequently quantified. We hypothesized that in patients with CVD undergoing cardiac magnetic resonance (CMR), liver T1-times indicate liver damage and are associated with cardiovascular outcome. Methods: We measured hepatic T1-times, displayed on standard cardiac T1-maps, in an all-comer CMR-cohort. At the time of CMR, we assessed validated general liver fibrosis scores. Kaplan-Meier estimates and Cox-regression models were used to investigate the association between hepatic T1-times and a composite endpoint of non-fatal myocardial infarction, heart failure hospitalization, and death. Results: 1022 participants (58±18 y/o, 47% female) were included (972 patients, 50 controls). Hepatic T1-times were 590±89ms in patients and 574±45ms in controls (p=0.052). They were significantly correlated with cardiac size and function, presence of atrial fibrillation, NT-pro-BNP levels, and gamma-glutamyl-transferase levels (p<0.001 for all). During follow-up (58±31 months), a total of 280 (29%) events occurred. On Cox-regression, high hepatic T1-times yielded a significantly higher risk for events (adj.HR 1.66 [95% CI: 1.45–1.89] per 100ms increase, p<0.001), even when adjusted for age, sex, left and right ventricular ejection fraction, NT-proBNP, and myocardial T1-time. On restricted cubic splines, we found that a hepatic T1-time exceeding 610ms was associated with excessive risk. Conclusion: Hepatic T1-times on standard CMR scans were significantly associated with cardiac size and function, comorbidities, natriuretic peptides, and independently predicted cardiovascular mortality and morbidity. A hepatic T1-time >610ms seems to indicate excessive risk. Funding Acknowledgement: Type of funding sources: None.